In vitro Intestinal Mucosal Epithelial Responses to Wild-Type Salmonella Typhi and Attenuated Typhoid Vaccines - Fiorentino, Maria; Lammers, Karen M.; Levine, Myron M.; Sztein, Marcelo B.; Fasano, Alessio (Frontiers in Immunology, 2013)
Typhoid fever, caused by S. Typhi, is responsible for approximately 200,000 deaths per year worldwide. Little information is available regarding epithelium-bacterial interactions in S. Typhi infection. We have evaluated in vitro the effects of wild-type S. Typhi, the licensed Ty21a typhoid vaccine and the leading strains CVD 908-htrA and CVD 909 vaccine candidates on intestinal barrier function and immune response. Caco2 monolayers infected with wild-type S. Typhi exhibited alterations in the organization of tight junctions, increased paracellular permeability, and a rapid decrease in Trans-Epithelial Electrical Resistance as early as 4h post-exposure. S. Typhi triggered the secretion of interleukin (IL)-8 and IL-6. Caco2 cells infected with the attenuated strains exhibited a milder pro-inflammatory response with minimal disruption of the barrier integrity. We conclude that wild-type S. Typhi causes marked transient alterations of the intestinal mucosa that are more pronounced than those observed with Ty21a or new generation attenuated typhoid vaccine candidates.